Ekstrak Cocor Bebek terhadap Kadar TNF-Î± pada Plasenta, Tekanan Darah, Albumin Urine pada Lupus Bunting: Extra Cocor Duck on TNF-Î± Levels on Placenta, Blood Pressure, Urine Albumin in Lupus - Sofia Mawaddah (Politeknik Kesehatan Kemenkes Mamuju, 2019)
Cocor duck plants contain alkaloids, flavonoids, phenolic compounds, tannins, vitamins, macro and micro elements, lemon acid, apple acid, vitamin C, quercetin-3-diarabenoside and kaemferol-3-glucoside. Inside the duck duck, there is a flavonoid which is a natural phenolic compound which has potential as an antioxidant and has bioactivity as a medicine or as an herbal medicine to treat LES. The aim of the study was to determine the effect of duck cocor extract on TNF-Î± levels in the placenta, blood pressure and urine albumin in the Balb/c lupus pregnant mice model. Female BALB/c mice were injected pristan 0.5 ml, after 12 weeks of ANA examination, if the test was positive then the mice were pregnant. Pregnant lupus mice were given Coco Duck extract in three different doses: 10.5 mg/day, 21 mg/day and 42 mg/day orally every day for 10 days of pregnancy. The percentage of TNF-Î± was examined by the ELISA method, MAP was examined using COD and urine albumin was examined by the ELISA method. The results of the study are there are effects of giving cocor duck extract on TNF-Î± levels. Doses of 10.5 mg/day and 42 mg/day have the ability to reduce TNF-Î± levels. Meanwhile, in blood pressure and urine albumin, Cocor Duck extract was not able to reduce significantly. Cocor duck leaf extract can significantly reduce TNF-Î± levels. Cocor duck leaf extract is unable to reduce urine albumin levels and blood pressure. The remedy for dealing with LES is very limited, therefore extra cocor duck leaves can be used as an alternative treatment for LES.